BIODIVERSITY OVERVIEW OF SODA PANS IN THE VOJVODINA REGION (SERBIA) - Bojan Gavrilović; Miloš Ćirić; Aleksandra Vesić; Danijela Vidaković; Boris Novaković; Milica Živanović (Zbornik Radova: Geografski institut "Jovan Cvijić", 2018)
Due to their specific physical and chemical properties of water and soil soda pans of the Vojvodina region represent a unique type of habitats. Salinity is a major structuring factor which strongly affects species richness. Many halotolerant, alkalotolerant and halophilic organisms, together with numerous eurytopic elements inhabit these kinds of ecosystems. In this review we tried to compile the biodiversity information from various literature sources and give the best representation of what can be expected to be found in these shallow, temporary and intermittent aquatic environments. Only a few groups of organisms are fairly well studied, while many others are insufficiently investigated or the knowledge of them is lacking altogether. Best investigated are certain groups of algae and birds. Bacterial communities, as well as many invertebrate groups, are poorly studied or not investigated at all. Characteristic elements of flora and fauna, together with growing anthropogenic pressures make soda pans prime targets for protection.